Experimental investigations and laser based validation measurements in a gas turbine model combustor. (12th May 2004) - Duan, X.R.; Weigand, P.; Meier, W.; Keck,, O.; Stricker, W.; Aigner, M.; Lehmann, B.
A swirled CH4 /air diffusion flame has been operated in a gas turbine model combustor at the lean blow-off limit. Laser Doppler velocimetry, planar laser-induced fluorescence of OH and CH, and laser Raman scattering were applied in order to measure velocities, flame structures, and the joint probability density functions of major species concentrations, mixture fractions and temperatures. The main goals of the investigations were a better understanding of the complex physical and chemical processes in flames with swirl, e.g., mixing, stabilisation, heat release, and finite-rate chemistry effects, and the generation of an extensive data base for the validation of numerical flame codes.